Inactivation of SARS-CoV-2 in the Liquid Phase: Are Aqueous Hydrogen Peroxide and Sodium Percarbonate Efficient Decontamination Agents? - Mileto, Davide; Mancon, Alessandro; Staurenghi, Federica; Rizzo, Alberto; Econdi, Stefano; Gismondo, Maria Rita; Guidotti, Matteo (ACS Chemical Health & Safety., 2021)
A diluted 3% w/w hydrogen peroxide solution acidified to pH 2.5 by adding citric acid inactivated SARS-CoV-2 virus by more than 4 orders of magnitude in 5 min. After a contact time of 15 min, no viral replication was detected. Aqueous solutions of sodium percarbonate inactivated coronavirus by >3 log diminution in 15 min. Conversely, H O solutions with no additives displayed a scarce virucidal activity (1.1 log diminution in 5 min), confirming that a pH-modifying ingredient is necessary to have a H O -based disinfectant active against the novel coronavirus.